Human Immuno-Deficiency Virus co-infection in suspected TB patients - Sherchand, JB; Maharjan, S; Bam, DS; Singh, A; Cuevas, LE (Journal of Institute of Medicine Nepal, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Introduction: Tuberculosis is one of the major public health problems in Nepal and HIV has become the most potent risk factor for the progression of TB infection as HIV-positive people are more likely to develop TB when newly infected or reinfected with Mycobecterium tuberculosis. Our main aim was to determine TB/HIV co-infection cases visiting DOTS center and Research center. Materials and Methods: The study was conducted in DOTS center of TUTH, Maharajgunj and Infectious and Tropical Disease Research and Prevention Center, Tripureshwor. We included a total of 300 patients with the respiratory tract symptoms and cough more than 3 weeks suggesting the symptom of pulmonary tuberculosis and having risk behaviour towards HIV infection. They were interviewed with a structured questionnaire during October 2006 to July 2007. All of them were screened for tuberculosis by sputum microscopy, AFB culture, radiology and HIV infection by standard ELISA method. Results: Among 300 suspected TB patients, 79 were diagnosed as pulmonary TB positive patients and 34 as HIV seropositive. The coprevalence of TB/HIV was 4.33 percent (13/300) among total patients among which 12 males and 1 female were found to be coinfected with TB/HIV. Conclusion: HIV co-infection in pulmonary TB positive cases was 16.46 percent (13/79), which revealed it as an alarming situation in developing countries, like Nepal. More cases were found in young adults aged range from 21-40. Males were found to be more infected than female. Key words: TB, HIV, Co-infection, DOTS, ELISA Journal of Institute of Medicine, April, 2008; 30:1 6-10 The full text of this paper is available from the Journal of Institute of Medicine website